Evaluasi Kapasitas Parkir SD Muhamadiyah 6 Kota Palembang - Sari, Nadra Mutiara; Susetyo, Dimas Ariezky; Aszharri, Arief; Azni, Rakmani; Srikandi, Ghina Rahma (Jurnal Talenta Sipil, 2025)
Muhammadiyah 6 Elementary School, Palembang City, is one of the schools located on Jalan Jendran Sudirman, which is right in front of the main road. As a result, many parents dropping their children off at school stop on the roadside. Parking on the roadside around Muhammadiyah 6 Elementary School, Palembang, has caused significant traffic congestion, especially during the morning rush hour (6:00–7:00 AM) and afternoon rush hour (2:30–3:00 PM). This is because the existing parking facilities at the school do not meet the parking needs of vehicles. Therefore, an evaluation is needed regarding the parking capacity needs at the elementary school. The method used is a descriptive method with an inductive approach, through a field survey at 6:30–3:00 PM. The survey results show that the average daily number of vehicles entering and leaving the location is 1,472 motorcycles and 567 cars. The need for parking space reaches 149,3184 m² for motorcycles and 322,368 m² for cars, but the available land is only 105.75 m² for motorcycles and 280 m² for cars. Therefore, it can be concluded that there is a need for additional parking space or a pick-up and drop-off system by parents/guardians of students to prevent vehicles from stopping on the road and allow for smooth and orderly traffic flow